A new method for reliability allocation of avionics connected via an airborne network. (February 2015) - Li, Ruiying; Wang, Jingfu; Liao, Haitao; Huang, Ning
Abstract: Avionics are connected via an airborne network, and the realization of their functions depends on successful data transmission through the network. Once the system reliability goal has been defined, reliability allocation must be performed to the subsystems and components. However, the widely used reliability allocation methods are not capable of dealing with complex connections between avionic subsystems. In this paper, an improved Advisory Group on the Reliability of Electronic Equipment (AGREE) allocation method is proposed for multi-mission networked avionics. In the proposed procedure, both the complexity and the importance of components are explicitly considered. Analytic algorithms and Monte Carlo simulation are applied to calculate the reliability of such a complex network structure. To determine the reliability allocation values, a heuristic algorithm is proposed, and an allocation adjustment procedure is provided to avoid inconsistent allocations caused by the same category of components involved in multiple missions of avionics. Our numerical study on A380 avionics, whose data are transmitted through Avionics Full Duplex Switched Ethernet (AFDX), shows that the proposed method is practical and quite efficient in handling such complex reliability allocation problems. Abstract : Highlights: We propose a heuristic algorithm to allocate reliability for networked systems whose component importance is unknown. Analytic algorithms and Monte Carlo simulation are applied to determine the reliability for the complex networked structure. An adjustment method is provided to avoid inconsistency caused by the same component category involved in multiple missions. The system reliability goal is allocated objectively based on complexity and importance of components.